Analyzing The Modal Shift From Private Vehicles To Bicycles Through The Stated Preference Method: A Case Study Of Bicycle Lane Planning At Universitas Muhammadiyah Yogyakarta - Wardani, Ayu; Rambak, Ezra Pasereng; Rahman, La; Badia, Bahdin Ahad; Muchlisin, Muchlisin (Sultra Civil Engineering Journal (SCiEJ), 2025)
Urban transportation systems face increasing challenges due to traffic congestion, air pollution, and the overreliance on private vehicles. Promoting a shift to more sustainable transport modes, such as bicycles, is one strategy to address these issues. This study analyzes the potential for a modal shift from private vehicles to bicycles among students at Universitas Muhammadiyah Yogyakarta. Using the Stated Preference (SP) method, data were collected through questionnaires to assess individuals' willingness to switch transport modes under various scenarios, such as improvements in cycling infrastructure, safety, and travel time. The analysis identifies key factors that influence mode choice and estimates the probability of modal shift under different policy interventions. The findings provide essential insights for urban planners and university stakeholders in developing effective bicycle lane networks and supporting facilities. The study concludes that with adequate infrastructure and supporting policies, the potential for bicycle use on campus can be significantly increased